Labor competencies and the functions of the social worker, Toromocho, mining-Chinalco, Yauli-La Oroya-Junín 2019 - Rojas Santivañez, Nataly Noelia (2023)
The article entitled: Labor competencies and the functions of the social worker, Toromocho, Minera-Chinaco, Yauli, La Oroya-Junín 2019, aimed to determine the relationship between the focus on labor competencies and the functions of the social worker. The methodology used was: Method: Hypothetical Deductive. Approach: Quantitative. Scope: descriptive-correlational; descriptive. Research design was: Non-experimental, the study article consisted of 26 professionals in the field of social work. For validation, Cronbach's Alpha and expert judgment criteria were used. The results of the study show the existence of a direct and significant relationship between job competencies and the development of the functions of the social worker; Starting from the “Spearman's Rho” test, with a bilateral probability value of less than the established significance value (α = 0.05), it is possible to specify that the magnitude of this correlation is 83.2% (.832). , corresponds to a strong positive correlation; It is concluded that the correlation between job skills and the development of the functions of the social worker is positive and moderate. The result focuses on the perception that society has about the role played by the social worker in the mining company, valuing professional skills.